2011
DOI: 10.1159/000334278
|View full text |Cite
|
Sign up to set email alerts
|

Long-Segment Type 1 Split Cord Malformation with Two-Level Split Cord Malformation and a Single Dural Sac at the Lower Split

Abstract: Objective and Importance: Two-level bony spurs are rare and also a very long segment of bony spur is very rare. Bony spur with a single dural covering is not reported in the literature. Here, we report a case of prophylactic surgery performed on a patient with a bony spur with a single dural covering who showed a good postoperative outcome. This case highlights the importance of prophylactic surgery in such patients to avoid cord injuries. Clinical Presentation: Since birth a 1-year-old child had had a tuft of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, some authors have reported a few cases with characteristics of both types I and II SCM, meaning that the lesion incorporated the hemicords within a single dural sac and an extradural partial bony septum 1,3,5,7,8,15,18,19,21) . We reviewed the literature, and 13 pertinent cases are listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, some authors have reported a few cases with characteristics of both types I and II SCM, meaning that the lesion incorporated the hemicords within a single dural sac and an extradural partial bony septum 1,3,5,7,8,15,18,19,21) . We reviewed the literature, and 13 pertinent cases are listed in Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of type I SCM with single dural sheath is reported in English literature to the best of our knowledge, that too by the senior author of this paper (Mahapatra). [ 2 ] In previous patient, authors reported a long-segment type 1 split cord malformation, with two-level split cord malformation and a single dural sac and the spur was at the lower end of split. There was a bony spur arising from the D 11 body level without a separate dural covering but with 2 cords.…”
Section: Discussionmentioning
confidence: 99%
“…Only one case of single dural sheath in type 1 SCM has been reported in English literature till now. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…The article by Singh et al [1] entitled ‘Long-term segment type 1 split cord malformation with two-level split cord malformation and a single dural sac at the lower split’ aroused our interest when reading it. The authors report a case of two-level type 1 split cord malformation (SCM) with a low-lying conus at the L3–4 level.…”
mentioning
confidence: 99%
“…One of the weak points of this theory is composite-type SCM. Although it has not been proven yet, the multiple accessory neuroenteric canal was considered to be responsible for the development of composite-type SCM [1,2,3,4,5]. However, there are two questions concerning this theory.…”
mentioning
confidence: 99%